Parliamentary Scrutiny of the European Semester: The Case of Poland - Schweiger, Christian (2021)
The European Semester became an essential part of the revised governance architecture of the Europe 2020 reform strategy for the Single European Market under the conditions of the global financial crisis and the emerging eurozone crisis a decade ago. The article examines to what extent the European Semester offers channels to establish throughput legitimacy by granting national parliaments the ability to effectively scrutinise executive decision-making in the annual policy cycle. Poland is chosen as the case study for parliamentary scrutiny of the EU’s system of multi-level governance in the East-Central European region. The analysis adopts a liberal intergovernmentalist two-level approach. On the domestic level it concentrates on the involvement of the Sejm, the lower house of parliament, on the drafting of the Polish National Reform Plans for the annual Semester policy cycle between 2015 and 2020. The basis for the analysis are official transcripts from the plenary debates in the relevant committees, the European Affairs Committee and the Public Finance and the Economic Committee. The Polish case study illustrates that the European Semester represents a predominantly elite-driven process of policy coordination, which is strongly geared towards EU-level executive bargaining processes between national governments and the European Commission at the expense of domestic parliamentary scrutiny.